2005
DOI: 10.1002/eji.200526141
|View full text |Cite
|
Sign up to set email alerts
|

IFN-γ-producing human T cells directly induce osteoclastogenesis from human monocytes via the expression of RANKL

Abstract: The current study explored our hypothesis that IFN-c-producing human T cells inhibit human osteoclast formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
91
0
6

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 127 publications
(100 citation statements)
references
References 41 publications
3
91
0
6
Order By: Relevance
“…RANKL + CD4 + PB T cells isolated from patients with early RA, if cultured with monocytes for 2 wk at a high T cell:monocyte ratio (4:1), can induce osteoclast differentiation (41). Other studies have shown that activated PB T cells induce RANKL-dependent osteoclastogenesis from adherent PBMCs if these cultures are pretreated with M-CSF (40,42). Although a direct role for T cells in inducing osteoclastogenesis remains controversial, recent studies have established an indirect role for the Th17 cell subset that up-regulates RANKL expression by osteoblasts (43).…”
Section: Discussionmentioning
confidence: 99%
“…RANKL + CD4 + PB T cells isolated from patients with early RA, if cultured with monocytes for 2 wk at a high T cell:monocyte ratio (4:1), can induce osteoclast differentiation (41). Other studies have shown that activated PB T cells induce RANKL-dependent osteoclastogenesis from adherent PBMCs if these cultures are pretreated with M-CSF (40,42). Although a direct role for T cells in inducing osteoclastogenesis remains controversial, recent studies have established an indirect role for the Th17 cell subset that up-regulates RANKL expression by osteoblasts (43).…”
Section: Discussionmentioning
confidence: 99%
“…46 In this regard, activated IFN-␥-producing Th1 cells themselves express RANKL, induce osteoclastogenesis, and mediate infection-stimulated alveolar bone resorption. 47,48 Additional studies will be needed to precisely determine the pathways leading to bone resorption in Th1-biased animals.…”
Section: Discussionmentioning
confidence: 99%
“…11,12) In light of this, we previously reported that diarylheptanoid hirsutenone (HTN), 1,7-bis-(3,4-dihydroxyphenyl)-4-heptene-3-one and one of the major diarylheptanoids, isolated from the bark of Alnus japonica. Cumulative evidences suggest that HTN has bioactive properties as a diarylheptanoid and plays a key role in inducing tumor necrosis factor-related apoptosis-inducing ligand (TRAIL)-dependent apoptosis and in the inhibition of T cell-dependent cytokines, such as IL-2, 4, 5, 10, 13, and IFNγ.…”
Section: )mentioning
confidence: 99%
“…9,10) In addition, an increasing body of evidence has focused on activated T cell-derived IFNγ for the induction of osteoclastogenesis, although IFNγ has also been shown to have a direct anti-osteoclastogenic effect via the suppression of RANKL signaling and the subsequent degradation of tumor necrosis factor receptor-associated factor 6 (TRAF6). 11,12) In light of this, we previously reported that diarylheptanoid hirsutenone (HTN), 1,7-bis-(3,4-dihydroxyphenyl)-4-heptene-3-one and one of the major diarylheptanoids, isolated from the bark of Alnus japonica. Cumulative evidences suggest that HTN has bioactive properties as a diarylheptanoid and plays a key role in inducing tumor necrosis factor-related apoptosis-inducing ligand (TRAIL)-dependent apoptosis and in the inhibition of T cell-dependent cytokines, such as IL-2, 4, 5, 10, 13, and IFNγ.…”
mentioning
confidence: 99%